Sperm maturation in sturgeon (Actinopterygii, Acipenseriformes): A review - Dzyuba, Borys; Cosson, Jacky; Dzyuba, Viktoriya; Fedorov, Pavlo; Bondarenko, Olga; Rodina, Marek; Linhart, Otomar; Shelton, William L; Boryshpolets, Sergii (Theriogenology, 2017)
The morphology of the reproductive system of acipenseriform fishes is quite different from that of teleostean species, but an associated unique physiological difference in male sturgeons was not discovered until recently; sperm of sturgeons passes through the kidneys then via Wolffian ducts into the environment rather that emptying directly through seminal ducts. The mixing of sperm with excretory products has been found to be a requisite for the capacity to be activated (maturation step) instead of being deleterious. In the current review we summarize results of studies performed in our laboratory on physiological processes involved in sturgeon sperm maturation, namely changes in: 1) ionic environment; 2) sensitivity of spermatozoa to calcium ions (Ca2+); 3) antioxidant enzymes and proteolytic activities; and 4) content in macroergic phosphates arising during this maturation process. We also discuss taxa-specific aspects of sturgeon sperm maturation in relation to hormonal regulation of spermiation, and the unusual features of sturgeon sperm maturation relative to using testicular sturgeon sperm in aquaculture.
Keywords: Sperm Maturation; Wolffian ducts; Urine; mužské pohlavní orgány; mužské pohlaví; Fishes; Fish seminal fluid; zvířata; zrání spermie; ryby; Spermatozoa; Urogenital system; Post-testicular maturation; Sperm motility; spermie; Male; Genitalia, Male; Animals